First report of seroprevalence of Toxoplasma gondii and Neospora caninum in dairy sheep from Humid Pampa, Argentina - Hecker, Yanina Paola (2013)
The aim of this study was to describe the occurrence of antibodies to Toxoplasma gondii and Neospora caninum in dairy sheep from the Humid Pampa region, Argentina. Blood samples from 704 dairy sheep belonging to six flocks were collected. Using a cut off titer of 1:50, an indirect fluorescence antibody test was used. Antibodies to T. gondii or N. caninum were detected in 17.3 % (n = 122) and 3 % (n = 21), respectively. All the flocks had at least one seropositive animal to T. gondii but two of them had no seropositive sheep to N. caninum. Fifty-two of 122 (42.6 %) positive samples to T. gondii had antibody titers higher than 1:400. There was a significantly higher proportion of T. gondii seropositive animals in females and older sheep (p < 0.05). Ten of 21 (52.3 %) positive samples to N. caninum had antibody titers higher than 1:400. This is the first report of seroprevalence of T. gondii and N. caninum in dairy sheep from Humid Pampa, Argentina. Further research is required for a better understanding of the role of toxoplasmosis and neosporosis in dairy sheep in Argentina.